Implementing Epic Beaker Laboratory Information System for Diagnostics in Anatomic Pathology - Sergi CM (Dove Medical Press, 2022)
Consolato M Sergi1,2 1Anatomic Pathology Division, Children's Hospital of Eastern Ontario, University of Ottawa, Ottawa, ON, Canada; 2Deparment of Laboratory Medicine and Pathology, University of Alberta, Edmonton, AB, CanadaCorrespondence: Consolato M Sergi, Tel +1 613-737-7600 x 2427, Fax +1 613-738-4837, Email csergi@cheo.on.caAbstract: Medicine is expeditiously evolving, and the number of diagnostic opportunities has increased exponentially in the last decade. Electronic medical records (EMRs) have been welcomed in most institutions worldwide following an early period of suspicious behavior. Unfortunately, several cracks dictated the initial approach to hospital systems and leadership incompetency. However, the pathway for a successful decade of EMRs is paved. This narrative review illustrates some principles implementing Epic Beaker software for anatomic pathology in academic medical institutions. Implementing such software improves the diagnostic approach in the division of anatomic pathology because the pathologists can directly access an enormous amount of clinical and radiological information now at their front desk using extremely versatile windows.Keywords: diagnostics, laboratory information system, Epic, Beaker, quality assurance